Activities and conformation changes of food enzymes induced by cold plasma: A review. Issue 5 (9th March 2019) - Han, Yongxu; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: Food endogenous enzymes have impacts on color, texture and flavor of foods during food processing or preservation. Cold plasma is a novel non-thermal food processing technology, which has been extensively studied for contamination elimination and shelf life extension of foods. Particularly, much work has been reported about the effects of cold plasma on enzyme activities and alterations about enzymes conformational structures. It is thus necessary to understand the mechanisms of actions and applications of cold plasma technology in the conformation of food endogenous enzymes. This review focuses on the applications of cold plasma for the inactivation of various endogenous enzymes, including peroxidase, polyphenol oxidase, lysozyme, α-chymotrypsin, alkaline phosphatase, and pectin methylesterase. The activations of several enzymes, such as superoxide dismutase, catalase, and lipase, by cold plasma are also discussed. In addition, this review highlights the transformation of conformational structures including primary and spatial structures induced by chemical reactive species during cold plasma treatments, such as reactive oxygen species and reactive nitrogen species, especially, active sites consisting of prosthetic group and specific amino acids are demonstrated. Both extrinsic and intrinsic factors affecting cold plasma treatments are also described. In general, cold plasma exhibits the ability to activate or inactivate enzymes activities with affecting the conformational structures of enzyme. Further studies should be focused on exploration at molecular level for providing more insight on the interaction mechanism. In addition, equipment and process parameters of cold plasma operation for different fresh food products should be optimized for achieving appropriate control on enzyme variation and obtaining maximum efficiency.